In the land of Ninkasi: a history of beer in Mesopotamia - Paulette, Tate (Oxford University Press, 2024)
"In the Land of Ninkasi: A History of Beer in Mesopotamia presents the narrative surrounding the world's first great beer culture. It focuses on the beers of ancient Mesopotamia while also considering the people who brewed and drank them and the places where they were drunk. The clear roadmap into the ancient source material provides insights from archaeological remains, ancient works of art, and cuneiform texts. Moreover, narrative vignettes and thought experiments were used to analyze and interpret the culture of beer drinking in ancient Mesopotamia. Additionally, In the Land of Ninkasi provides an overview of drinking styles, brewing equipment, and the gods and goddesses who governed the lives of people."